2020
DOI: 10.1360/tb-2020-1035
|View full text |Cite
|
Sign up to set email alerts
|

The use and change of emotion regulation strategies: The promoting effect of cognitive flexibility

Abstract: The progress of emotion regulation methods and paradigms: From voluntary emotion regulation to automatic emotion regulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Second, it has been suggested that emotion regulation flexibility is a subset of cognitive flexibility 85 and that it may be a specific manifestation of cognitive flexibility in changing regulation strategies according to the context, facilitating individuals to respond differently to changing situations. 16 However, whether cognitive flexibility has an indirect or direct effect on individuals’ emotional responses requires further empirical investigation. It is important to note that greater flexibility in emotion regulation choices is not better, and too much flexibility may reflect hypersensitivity or instability to situations.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Second, it has been suggested that emotion regulation flexibility is a subset of cognitive flexibility 85 and that it may be a specific manifestation of cognitive flexibility in changing regulation strategies according to the context, facilitating individuals to respond differently to changing situations. 16 However, whether cognitive flexibility has an indirect or direct effect on individuals’ emotional responses requires further empirical investigation. It is important to note that greater flexibility in emotion regulation choices is not better, and too much flexibility may reflect hypersensitivity or instability to situations.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Second, it has been suggested that emotion regulation flexibility is a subset of cognitive flexibility 85 and that it may be a specific manifestation of cognitive flexibility in changing regulation strategies according to the context, facilitating individuals to respond differently to changing situations. 16 However, whether cognitive flexibility has an indirect or…”
Section: Summary and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the individual level, cognitive flexibility is a general cognitive tendency, which means people have the consciousness, willingness, and efficacy to make flexible choices in any situation ( Martin and Rubin, 1995 ). Studies have found that people with high cognitive flexibility are more able to effectively use multiple emotional regulation strategies ( Gao et al, 2021 ), while people with better emotional regulation ability are more able to reduce the impact of other’s emotions on themselves ( Eisenberg and Fabes, 1992 ; Lockwood et al, 2013 ). At the same time, cognitively flexible people experienced lower levels of depression after adverse events ( Wang and Liu, 2017 ).…”
Section: Introductionmentioning
confidence: 99%